On the role of prudence in the virtue ethics of Thomas Aquinas - Francesco Malaguti (Ethic@: an International Journal for Moral Philosophy, 2025)
The paper is about the ethics of Thomas Aquinas, and focuses especially on the concept of Prudence, one of the four cardinal virtues according to Christian thought. The study considers the debt of the medieval philosopher to ancient philosophy (especially Aristotle) and the previous authorities of the Christian intellectual tradition, reconstructing Aquinas’ conception of Prudence.